Navigation Techniques for Zoomable Treemaps - Renaud Blanch; Éric Lecolinet (UIST'06: Adjunct Proceedings of the Annual ACM Symposium on User Interface Software and Technology, 2006)
This paper presents a new technique called zoomable treemaps that makes it possible to navigate in very large trees. It integrates several efficient interaction techniques that enable multi-scale and structure-aware navigation.